A framework of current based defibrillation improves defibrillation efficacy of biphasic truncated exponential waveform in rabbits - Weiming Li (Nature Portfolio, 2021)
Abstract Defibrillation is accomplished by the passage of sufficient current through the heart to terminate ventricular fibrillation (VF). Although current-based defibrillation has been shown to be superior to energy-based defibrillation with monophasic waveforms, defibrillators with biphasic waveforms still use energy as a therapeutic dosage. In the present study, we propose a novel framework of current-based, biphasic defibrillation grounded in transthoracic impedance (TTI) measurements: adjusting the charging voltage to deliver the desired current based on the energy setting and measured pre-shock TTI; and adjusting the pulse duration to deliver the desired energy based on the output current and intra-shock TTI. The defibrillation efficacy of current-based defibrillation was compared with that of energy-based defibrillation in a simulated high impedance rabbit model of VF. Cardiac arrest was induced by pacing the right ventricle for 60 s in 24 New Zealand rabbits (10 males). A defibrillatory shock was applied with one of the two defibrillators after 90 s of VF. The defibrillation thresholds (DFTs) at different pathway impedances were determined utilizing a 5-step up-and-down protocol. The procedure was repeated after an interval of 5 min. A total of 30 fibrillation events and defibrillation attempts were investigated for each animal. The pulse duration was significantly shorter, and the waveform tilt was much lower for the current-based defibrillator. Compared with energy-based defibrillation, the energy, peak voltage, and peak current DFT were markedly lower when the pathway impedance was > 120 Ω, but there were no differences in DFT values when the pathway impedance was between 80 and 120 Ω for current-based defibrillation. Additionally, peak voltage and the peak current DFT were significantly lower for current-based defibrillation when the pathway impedance was < 80 Ω. In sum, a framework of adjusting the charging voltage and shock duration to deliver constant energy for low impedance and constant current for high impedance via pre-shock and intra-shock impedance measurements, greatly improved the defibrillation efficacy of high impedance by lowering the energy DFT.